Digestion of cooked meat proteins is slightly affected by age as assessed using the dynamic gastrointestinal TIM model and mass spectrometry. Issue 6 (17th May 2016) - Denis, S.; Sayd, T.; Georges, A.; Chambon, C.; Chalancon, S.; Santé-Lhoutellier, V.; Blanquet-Diot, S.
Abstract : The main goal of the present study was to compare the degradation of meat proteins in adult and elderly digestive conditions. Abstract : In humans, meat ensures the supply of proteins with high nutritional value and indispensable amino acids. The main goal of the present study was to compare the degradation of meat proteins in adult and elderly digestive conditions. Cooked meat was subjected to in vitro digestion in the dynamic multi-compartmental TIM (TNO gastroIntestinal Model) system. Digestibility and bioaccessibility were determined using nitrogen balance and digestion products were identified using mass spectrometry. The TIM model was adapted according to in vivo data to mimic the specific digestive conditions of elderly people. Meat protein digestibility and bioaccessibility were around 96 and 60% respectively and were not influenced by age ( P > 0.05). As much as 800 peptides were identified in the duodenal and jejunal compartments issued from 50 meat proteins with a percentage of coverage varying from 13 to 69%. Six proteins, mainly from the cytosol, were differentially hydrolyzed under the adult and elderly digestive conditions. Pyruvate kinase was the only protein clearly showing a delay in its degradation under elderly digestive conditions. This study provides significant insights into the understanding of meat protein dynamic digestion. Such data will be helpful to design in vivo studies aiming to evaluate dietary strategies that can attenuate muscle mass loss and more generally maintain a better quality of life in the elderly population.